Estimating the longevity of glaciers in the Xinjiang region of the Tian Shan through observations of glacier area change since the Little Ice Age using high-resolution imagery. Issue 257 (22nd June 2020) - Liu, Julia; Lawson, Daniel E.; Hawley, Robert L.; Chipman, Jonathan; Tracy, Brian; Shi, Xun; Chen, Yaning
Abstract: Glacial retreat in response to warming climates in the arid Xinjiang region of northwestern China directly impacts downstream water resources available for local communities. We used high-resolution satellite imagery from 1969 to 2014 to delineate spatial changes in 54 active glaciers in the upper Kaidu River Basin in the Tian Shan as well as their past expanses during the Little Ice Age (LIA). We manually delineated their boundaries based on the interpretation of glacial, geomorphic and topographic features. From the total glacier surface area, we estimated glacier volume and mass. From 1969 to 2014, glacier area decreased by 10.1 ± 1.0 km 2 (relative loss of 34.2 ± 3.5%) and mass by 1.025 ± 0.108 Gt (relative loss of 43 ± 4.6%). From the LIA maximum (est. 1586 CE) to 1969, relative losses were less (25.7 ± 4.3% area loss and 33.1 ± 5.7% mass loss). Our results indicate that glacier recession is accelerating over time and that the glaciers are currently losing over 1.5 times more relative area than elsewhere in the Tian Shan. Using linear and non-linear projections, we estimate that these glaciers may disappear between 2050 and 2150 CE if climatic warming continues at the same pace.